A preliminary analysis on the effect of copper on Anopheles coluzzii insecticide resistance in vegetable farms in Benin - Talom, A.D.; Essoung, M.A.; Gbankoto, A.; Tchigossou, G.; Akoton, R.; Sahabi, B.B.A.; Atoyebi, S.M.; Fotso Kaute, A.; Verspoor, R.C.; Tamo, Manuele; Tchuinkam, T.; Lehman, G.L.; et al. (Springer, 2020)
The use of agrochemicals in vegetable production could influence the selection for insecticide resistance in malaria vectors. Unfortunately, there is a dearth of information on the potential contribution of agrochemicals to insecticide resistance in Anopheles mosquitoes breeding on vegetable farms in southern Benin. A Knowledge, Attitudes and Practices study was conducted with 75 vegetable farmers from Houeyiho and Seme to determine the main agrochemicals used in vegetable production, and the concentration and frequency of application, among other details. Mosquitoes and breeding water were sampled from the farms for analysis. Bioassays were conducted on mosquitoes, while breeding water was screened for heavy metal and pesticide residue contamination. Lambda-cyhalothrin was the main insecticide (97.5%) used by farmers, and Anopheles coluzzii was the main mosquito identified. This mosquito species was resistant (30–63% mortality rate) to λ-cyhalothrin. It was also observed that 16.7% of the examined breeding sites were contaminated with λ-cyhalothrin residues. Furthermore, copper contamination detected in mosquito breeding sites showed a positive correlation (r = 0.81; P = 0.0017) with mosquito resistance to λ-cyhalothrin. The presence of copper in λ-cyhalothrin-free breeding sites, where mosquitoes have developed resistance to λ-cyhalothrin, suggests the involvement of copper in the insecticide resistance of malaria vectors; this, however, needs further investigation.